Vaginal Probiotic Lactobacillus crispatus Seems to Inhibit Sperm Activity and Subsequently Reduces Pregnancies in Rat - Li, Ping; Wei, Kehong; He, Xia; Zhang, Lu; Liu, Zhaoxia; Wei, Jing; Chen, Xiaomei; Wei, Hong; Chen, Tingtao (Frontiers in Cell and Developmental Biology, 2021)
Background: Vaginal microbiota is associated with the health of female reproductive system and their offspring. Lactobacillus crispatus belongs to one of the most important vaginal probiotic while its role in the agglutination and immobilization of human sperm, fertility and offspring health is unclear. Methods: Adherence assays, sperm motility assays and Ca2+ detecting assays were used to analyze the adherence properties and sperm motility of L. crispatus, attenuated Salmonella typhimurium VNP20009, engineered S. typhimurium VNP20009 DNase I and Escherichia coli O157:H7 in vitro. The rat reproductive model was further developed to study the role of L. crispatus on reproduction and offspring health, using high-throughput sequencing, real-time PCR and molecular biology technique. Results: Our results indicated that L. crispatus, VNP20009, VNP20009 DNase I and E. coli O157:H7 significantly inhibited the sperm motility in vitro via adversely affecting the sperm intracellular Ca2+ concentration, and showed high adhesion to sperms (521 per 100 sperms). In vivo results indicated that L. crispatus and other tested bacteria greatly reduced the pregnancy rates, but L. crispatus had a positive effect on the maternal health and offspring development. Moreover, the transplantation of L. crispatus could sustain a normal bacterial composition of the vaginal microbiota in healthy rats, and markedly reduced the expression of uterine inflammatory factors (toll-like receptor-4/nuclear factor kappa-B, tumor necrosis factor-α, production of interleukin-1β etc.) and apoptosis factors (Fas Ligand, Bcl-2-associated X protein/B cell lymphoma-2 etc.) compared with the other tested strains. Conclusion: Our study demonstrated that the vaginal probiotic L. crispatus greatly affected the sperm activity and could also reduce pregnancies through its adhesion property, which might account for some unexplained infertility. Therefor, more cautious should be paid when used the L. crispatus as vaginal viable preparation in women of child-bearing age, especially for women whose partners with abnormal sperms.